2022
DOI: 10.7324/jabb.2023.110126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seven different wheat cultivars for their resistance to drought in terms of growth indicators and yield

Abstract: The study used a randomized complete block design with three replicates to investigate drought tolerance genes and wheat growth and yield. The experiment included seven wheat cultivars: Buhooth 158, Rasheed, Buhooth 22, Tahade, Fatih, N70, and Cimmyt 72 in main plots and three drought treatments: Irrigation after draining 50% of available water (D1), irrigation after draining 65% of available water (D2), and irrigation after draining 75% of available water (D3) in subplots. Drought treatments resulted in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
0
0
Order By: Relevance
“…The cultivar Furat had the most impact, with 50.78% under GS-V7 treatment, whereas cultivar the Konsens had the slightest effect, with 30.77%. These results were in analogy with the findings of AL-Fatlawi et al (2022), who identified the genotypes with drought tolerance.…”
Section: Grains Per Rowsupporting
confidence: 89%
“…The cultivar Furat had the most impact, with 50.78% under GS-V7 treatment, whereas cultivar the Konsens had the slightest effect, with 30.77%. These results were in analogy with the findings of AL-Fatlawi et al (2022), who identified the genotypes with drought tolerance.…”
Section: Grains Per Rowsupporting
confidence: 89%
“…Biofertilizers are vital in increasing the supply of nutrients, including nitrogen, which helped enhance vegetative growth, branch number, and flag leaf area, increasing biomass. The augmentation in biological yield can also refer to a positive correlation between plant height and biological yield (Farhood et al, 2022;Al-Fatlawi et al, 2023). These results were in analogy with the past findings concerning the evaluation of the capacity of phosphate-solubilizing bacteria and fungi on different forms of phosphorus in liquid culture (Turan et al, 2006, Schoebitz et al, 2013Al-Bahrani, 2015).…”
Section: Biological Yieldsupporting
confidence: 87%
“…According to Vargas-Ponce et al (2011), the application of molecular systematics has altered the view of the Tree of Life at the taxonomic level. Molecular markers, unaffected by external influences, have emerged as an influential resource for modern taxonomists (Al-Fatlawi et al, 2023). The internal transcribed spacer (ITS) of the rDNA and the ndhF and trnLF chloroplast areas are techniques used to analyze the phylogeny using short DNA sequences of standard genome genes.…”
Section: Introductionmentioning
confidence: 99%